Conceptual design of divertor and first wall for DEMO-FNS. (10th November 2015) - Sergeev, V.Yu.; Kuteev, B.V.; Bykov, A.S.; Gervash, A.A.; Glazunov, D.A.; Goncharov, P.R.; Dnestrovskij, A.Yu.; Khayrutdinov, R.R.; Klishchenko, A.V.; Lukash, V.E.; Mazul, I.V.; Molchanov, P.A.; et al.
Abstract: Key issues of design of the divertor and the first wall of DEMO-FNS are presented. A double null closed magnetic configuration was chosen with long external legs and V-shaped corners. The divertor employs a cassette design similar to that of ITER. Water-cooled first wall of the tokamak is made of Be tiles and CuCrZr-stainless steel shells. Lithium injection and circulation technologies are foreseen for protection of plasma facing components. Simulations of thermal loads onto the first wall and divertor plates suggest a possibility to distribute heat loads making them less than 10 MW m −2 . Evaluations of sputtering and evaporation of plasma-facing materials suggest that lithium may protect the first wall. To prevent Be erosion at the outer divertor plates either the full detached divertor operation or arrangement of the renewal lithium flow on targets should be implemented. Test bed experiments on the Tsefey-M facility with the first wall mockup coated by Ве tiles and cooled by water are presented. The temperature of the surface of tiles reached 280–300 °С at 5 MW m −2 and 600–650 °С at 10.5 MW m −2 . The mockup successfully withstood 1000 cycles with the lower thermal loading and 100 cycles with higher thermal loading.